Improving Student’s Vocabulary Using Information and Communications Technology - Yunda, Dede Dharma; Maulana, Danang Esha; Kurniawan, Ludi; Pham, Jennifer (International Journal of Contemporary Studies in Education, 2023)
Vocabulary is important in English and has become the primary communication skill in the teaching and learning process. Based on the several problems found, the researchers are interested in implementing ICT in learning English in the classroom. The use of ICT in this research is to make the students more efficient and interested in learning progress. This study has conducted using classroom action research (CAR). This study was conducted in MTs Muhammadiyah Karangkajen, Special Region of Yogyakarta. This study focuses on improving the vocabulary mastery of grade VIII students using ICT. This study was conducted in the first semester of the academic year of 2022/2023.The participants of this study were grade VIII-F students of MTs Muhammadiyah Karangkajen. Vocabulary, learning activities, creativity, students' sense of happiness, and their participation in class discussions were all highlighted as areas for improvement. Students' vocabularies tend to improve when visual media are used in the classroom. Students see positive impacts on the growth of their vocabulary mastery as a result of the use of ICT in the classroom.